2021
DOI: 10.21203/rs.3.rs-451910/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incorporating Interactive Workshops into Bedside Teaching: Completion of a Multi- Modal Rheumatology Rotation Significantly Increases Internal Medicine Residents’ Competency and Comfort with Comprehensive Knee Examinations

Abstract: Background: Studies have elucidated the lack of competency in musculoskeletal (MSK) examination skills amongst trainees. Various modalities have been studied, however, there remains a dearth of literature regarding the effectiveness of bedside teaching versus dedicated workshops. Our aim was to determine if incorporating a workshop into a rheumatology rotation would be effective in increasing medicine residents’ competency and comfort with knee examinations when compared to the rotation alone.Methods: Over 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Active learning was initially defined by Bonwell and Eison as anything that involves students "doing things and thinking about the things they are doing" (2). Multiple studies have since demonstrated better knowledge acquisition and retention when active learning is used than in traditional lectures (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Active learning was initially defined by Bonwell and Eison as anything that involves students "doing things and thinking about the things they are doing" (2). Multiple studies have since demonstrated better knowledge acquisition and retention when active learning is used than in traditional lectures (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%